PENYELAMATAN KEUANGAN NEGARA DARI PERSPEKTIF HUKUM PROGRESIF - YS, Masyitoh; Ratnawati, Elfrida (Universitas Ekasakti, 2023)
This research aims to explore how state financial recovery is carried out in Indonesia and analyze it using progressive law. Law enforcement against fraud in government activities is still a major problem in Indonesia. This fraud resulted in state losses, but the fines and compensation imposed were far below the value of state losses. The formulation of the problem is how is the state financial recovery carried out in Indonesia? and has the state's financial recovery considered a progressive legal approach? This research is a qualitative research, with normative research methods and carried out by means of literature studies. The data used is secondary data in the form of primary legal materials and secondary legal materials. This research shows that there is a disparity in sentencing that causes recovery against the impact of losses on state finances that is not optimal. The verdict of the panel of judges seems to only focus on the interests of punishing the perpetrators rather than recovering the victims. In conclusion, in law enforcement, punishment alone does not restore state losses, so it has not fulfilled the people's sense of justice. Progressive steps are needed from law enforcement officials to take action to save state finances which are the people's rights. This is in line with progressive legal theory and improves the image of law enforcement in Indonesia for the better through judge decisions that prioritize a sense of justice for the people.